The Role of the Samapta Unit in Handling Minor Crimes in Order to Reduce Illegal Liquor Circulation in the Kediri Police - Pratama, Muhammad Naufal Aji (Indonesian Journal of Police Studies, 2024)
The minor crime of illegal liquor at the Kediri Police was handled by the Samapta Unit of Kediri Regional Police and was the only minor crime case handled by the Samapta Unit in the last 4 years. This research was carried out with the aim of describing the mechanism of the Kediri Regional Police Satsamapta in handling minor crime of illegal alcohol, identifying the influence of Satsamapta’s role in handling minor crime of illegal alcohol distribution. The results of the research show that the mechanism for handling tipiring for illegal alcohol carried out by the Kediri Samapta Unit of Regional Police as a whole is in accordance with Perkabaharkam Number 6 of 2011 which is the applicable standard procedure. However, in the investigation process there are still inconsistencies with the Criminal Procedure Code. The role of Samapta Unit in handling minor crimes was measured by performance. It was found that in terms of quantity and timeliness, the Samapta Unit of Kediri Regional Police was good in its performance, but in terms of quality it was still not said to be good. The process of handling illegal alcohol tipping is influenced by supporting and inhibiting factors, which are contained in the components of legal structure, legal substance and legal culture.